Feminism in the works of Jamaica Kincaid - Ondeková, Elena (2006)
This thesis deals with three novels - Annie John, Lucy and An Autobiography of My Mother - by Jamaica Kincaid, a woman author of Caribbean descent. In order to prove that Jamaica Kincaid is a feminist author, I analyze the three novels from the point of view of feminism. There are many feminist features in all the novels, thus I have come to the conclusion that J. Kincaid is a feminist author.